2019
DOI: 10.1016/j.hpb.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The AKI Prediction Score: a new prediction model for acute kidney injury after liver transplantation

Abstract: Background: Acute kidney injury (AKI) is a frequent complication after liver transplantation. Although numerous risk factors for AKI have been identified, their cumulative impact remains unclear. Our aim was therefore to design a new model to predict post-transplant AKI. Methods: Risk analysis was performed in patients undergoing liver transplantation in two centres (n = 1230). A model to predict severe AKI was calculated, based on weight of donor and recipient risk factors in a multivariable regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 54 publications
5
46
3
Order By: Relevance
“…These findings were then further validated in the hospital cohort. Moreover, in the current study, the AUCs of PNI for AKI were 0.755 in the test cohort and 0.738 in the validation cohort, which were consistent with previous models for AKI in different populations (38,39).…”
Section: Discussionsupporting
confidence: 90%
“…These findings were then further validated in the hospital cohort. Moreover, in the current study, the AUCs of PNI for AKI were 0.755 in the test cohort and 0.738 in the validation cohort, which were consistent with previous models for AKI in different populations (38,39).…”
Section: Discussionsupporting
confidence: 90%
“…A previous study suggested that patients with BMI > 25 should get more attention even in patients with normal preoperative renal function [30]. Another study included recipient BMI as a predictor in their prediction model for AKI after liver transplantation [31]. In the study of Hilmi, weight > 100 kg was associated with the development of AKI within 72 h [5].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also investigated whether infusion of FFP is involved in the AKI. Kalisvaart et al found that FFP requirement during LT was the best predictor of post-transplant AKI [ 26 ]. In this study, FFP requirement was independently associated with AKI, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%